Therapeutic plasma exchange in acute liver failure. Issue 5 (26th July 2019) - Stahl, Klaus; Hadem, Johannes; Schneider, Andrea; Manns, Michael P.; Wiesner, Olaf; Schmidt, Bernhard M. W.; Hoeper, Marius M.; Busch, Markus; David, Sascha
Abstract: Background: Multi‐organ dysfunction in acute liver failure (ALF) has been attributed to a systemic inflammatory response directly triggered by the injured liver. High‐volume therapeutic plasma exchange (HV‐TPE) has been demonstrated in a large randomized controlled trial to improve survival. Here, we investigated if a more cost‐/ resource effective low‐volume (LV) TPE strategy might have comparable beneficial effects. Methods: This retrospective study evaluated the effect of LV‐TPE on remote organ failure, hemodynamical and biochemical parameters as well as on survival in patients with ALF. Twenty patients treated with LV‐TPE in addition to standard medical therapy (SMT) were identified and 1:1 matched to a historical ALF cohort treated with SMT only. Clinical and biochemical parameters were recorded at admission to the intensive care unit and the following 7 days after LV‐TPE. Results: Mean arterial pressure increased following first LV‐TPE treatments (d0: 68 [61‐75] mm Hg vs d7: 88 [79‐98] mm Hg, P = .003) and norepinephrine dose was reduced (d0: 0.264 [0.051‐0.906] μg/kg/min vs d3: 0 [0‐0.024] μg/kg/min, P = .016). Multi‐organ dysfunction was significantly diminished following LV‐TPE (CLIF‐SOFA d0: 17 [13‐20] vs d7: 7 [3‐11], P = .001). Thirty‐day in‐hospital survival was 65% in the LV‐TPE cohort and 50% in the SMT cohort (Hazard‐ratio for TPE: 0.637; 95% CI: 0.238‐1.706, P = .369). Conclusions: Patients treated with LV‐TPE showed improved surrogate parameters comparable with the effects reported with HV‐TPE. These data need to be interpreted with caution due to their retrospective character. Future controlled studies are highly desirable.